A REVIEW OF PENETRATION TUNGSTEN BASED PROJECTILE ON DEPTH OF PENETRATION AT ARMOR OF CERAMIC BASED - Abdul Basyir; Erna Shevilia Agustian; Adhistia Amelia (The Republic of Indonesia Defense University, 2020)
Nowadays, tungsten-based material is used for the core of projectile, while ceramic-based is used for the main material of armor. Tungsten-based material is chosen because it has density and hardness superior to steel based-material. Meanwhile, the ceramic-based can enhance mobility and resistance penetration of armor. Penetration of projectile on target generates an impact velocity parameter. This velocity has resulted when the projectile hits the target. Therefore, the value of impact velocity affects the quantity of depth of penetration (DoP) result. This paper reviews some papers regarding the penetration of tungsten-based projectile on ceramic-based armor. Furthermore, the content of these papers is reviewed by the narrative review method, and the impact velocity and DoP are the main data to analyze. Through this paper, impact velocity has a linear correlation with the DoP, the big of impact velocity produced bigger of DoP, and vice versa. Based on the data in this review, for the same impact velocity, material, and (almost) dimension of a projectile, SiC has better penetration resistance than B4C, TiB2, and Al2O3. Furthermore, the parameter of projectile dimension, projectile material type, target design, and material composition of the target also affects the DoP result.